Modelling longitudinal changes in isokinetic and isometric strength of the knee in adolescent soccer players - Duarte, J. P.; Philippaerts, R.; Valente-dos-Santos, J.; Seabra, A.; Coelho e Silva, M. J.; Malina, R. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: This study examined the contributions of growth, estimated body composition and skeletal maturity to developmental changes in isometric and isokinetic strength of the knee extensors and flexors in a mixed-longitudinal sample of youth soccer players. Methods: 67 Belgian players with chronological ages (CA) 10.5 to 13.6 years at baseline were followed on three to five occasions over five years. Stature, body mass, skinfold thicknesses, isometric strength of the knee extensors (ImKE) and knee flexors (ImKF), and isokinetic knee extension (IsoKE) and flexion (IsoKF) using a concentric protocol (180°/s) were measured. Skinfolds were used to predict % of fat; fat mass (FM) and fat-free mass (FFM) derived. Skeletal age (SA) was estimated with the TW2 RUS method. Multilevel random effects regression analyses were used to derive developmental polynomial models (MLwiN 2.02). Results: In four significant longitudinal models, an increase of 1 year in chronological age predicted 10.7N (ImKE), 2.7N (ImKF), 5.4N.m (IsoKE) and 2.7N.m (IsoKF), respectively. A gain of 1 kg of FM corresponded to an increment of 1.4N in ImKE, while a gain of 1 kg of FFM corresponded to an increase of 2.1N (ImKF), 1.4N.m(IsoKE) and 1.6 N.m (IsoKF). An SA classified as average (on time) or advanced (early) corresponded to advantage of 5.2N or 6.5N in ImKE, respectively. Discussion The different knee strength outputs had distinct developmental models across adolescence, but CA and CA squared were predictors in three of the four measures. SA contributed to longitudinal changes in isometric extensor strength, while body composition, especially FM, contributed to longitudinal changes in dynamic strength protocols. The results suggested a potentially important role for allometric multilevel modeling in partitioning effects attributed to indicators of body size, maturity status and training.